SASTRA ANAK UNTUK MEMBANGUN BUDAYA LITERASI - Octavian Muning Sayekti (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: The purpose of this paper is to peel the usefulness of children's literature to foster a culture of reading and writing or literacy. Low of literate culture that is now owned by the community can actually be grown with the introduction of children's literature since childhood. Giving the reading is within their child's stage of development will greatly assist the growth of their literacy. Literary readings will give effect to the child separately. This will have an impact on the child 's love of reading and writing skills to impact the. We know that two skills has relation.